THE INFLUENCE OF PSYCHOLOGY, PROFESSIONAL SCEPTICISM, AND AI ON AUDITOR PERFORMANCE WITH CONTINUOUS LEARNING MODERATION - Ariyanto, Sanusi; Azwirman, Azwirman; Sari, Zulfina Mayang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Purpose:This study looks at how different psychological factors, professional scepticism, and the use of artificial intelligence (AI) affect how well auditors perform.It also considers how continuous learning plays a role in influencing these effects. Method:We collected data through a survey from auditors working in Public Accounting Firms (KAP) and the Audit Board of Indonesia (BPK).We used a statistical method called Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the software SmartPLS 4 to analyze the data. Findings:Psychological traits like confidence and emotional stability strongly help improve auditor performance.Professional scepticism also has a positive effect on audit results. However, using AI has a negative impact, which might be because auditors are relying too much on it or not ready for the technology. Continuous learning helps make the positive effects of psychology and scepticism stronger and weakens the negative effect of AI use. Implications: Based on the Theory of Planned Behaviour (TPB), the study suggests that audit organizations should include training on psychological readiness, scepticism, and technology skills in their ongoing learning programs. Novelty: This study brings together human, professional, and technological aspects into one model with continuous learning as a key factor.It offers a more complete view of how auditors perform in an environment that is increasingly using technology